PENGARUH RETURN ON ASSET, FINANCIAL LEVERAGE, DAN TRADING VOLUME TERHADAP INITIAL RETURN - Sari, Meigia Nidya (UNIVERSITAS PEMBANGUNAN PANCA BUDI, 2020)
The research on the stock market and its returns has always been a hot topic to be discussed in a lot of financial literacy. The high investors interest in placing their capital in the stock market is a driving factor for these studies to be carried out continuously because it involves the interests of many people, especially for investors in obtaining profits and also for companies in developing the value of the company. Initial Return is the profit received by investors or shareholders who come from the difference price between the initial price of a stock purchased and the price of shares sold on the secondary market. Initial return can be influenced by many things such as return on assets, financial leverage, and trading volume, which will be analyzed for the effect on initial return in this research. There are 130 companies listed on the Indonesia Stock Exchange that were sampled in this research. Data collection techniques using census or saturated samples. Data were analyzed using multiple linear regression methods. Based on the results of data analysis, return on assets has no positive effect on Initial Return, while financial leverage has a positive effect on initial return, and trading volume has a negative effect on initial return. While these three variables together affecting initial return until 27,2%, and 72,8% affected by another variables.